Burden in caregivers of patients with functional dependence and its relation to spirituality - de Siqueira, Emanuely Andreoli; Bueno, Lucas Mateus Campos; de Almeida , Mariana Moskado Batista; de Oliveira, Ana Júlia Rodrigues; da Silva, Beatriz; Utida, Jussara Eliana; Pellizari, Camila Costa de Araújo; da Silva, Joyce Karla Machado; Silva, Igor Calixto da (Seven Editora, 2023)
Functional dependence is characterized by the limitation that the individual has to perform their activities of daily living, whether basic or complex, making it necessary a person to assist in performing these tasks (NARDI; SAWADA; SANTOS, 2013). DOI: https://doi.org/10.56238/colleinternhealthscienv1-050